Inclusive counterdestination. The discourse of Macri and Scioli on Facebook - Perez Zamora, Emmanuel (InMediaciones de la Comunicación, 2018)
In this paper we propose to discuss the destination and counterdestination in the political discourse of Mauricio Macri and Daniel Scioli during the presidential runoff period of the year 2015, in the Argentinian Republic. Our discursive object is formed from the posts made by both candidates in their official pages of the social network Facebook. To carry out our qualitative analysis we use interpretative tools booth the post-marxist focus of discourse that Laclau and Mouffe (2008, 2007, 2005, 2002, 1996, 1993, 1985) and the enunciative polyphony of García Negroni (2016, 1988). This study raises as a result the emergence of a new mode of counterdestination in the political discourse.